A Challenge Based Education Framework for Autonomous Shipping - Morariu, Andrei-Raoul; Tsvetkova, Anastasia; Bolbot, Victor; Sandell, Peter; Salokannel, Johanna; Saarni, Jouni; Isoaho, Jouni; Virtanen, Seppo (Sweden, 2026)
Due to expected profound changes in the maritime industry caused by the introduction of Maritime Autonomous Surface Shipping (MASS), the education in this field is in clear need of development. Cross-sectoral and inter-disciplinary understanding of the premises of autonomous shipping is required of professionals connected to MASS design, construction and operation. There is a gap in aligning education to technological developments in MASS, as existing approaches fail to specify the type of training required or to propose a framework for developing the future skills of seafarers. This paper addresses this gap by developing a framework for challenge-based education, emphasizing interdisciplinary knowledge and 21st-century skills such as critical thinking, problem solving, digital literacy, creativity, and communication. This framework allows for agile adjustments to meet the evolving and emerging needs of the maritime sector. The framework utilises genuine challenges of the maritime cluster that are defined in cooperation with maritime stakeholders and industry. The framework is customisable and it can be generalised to other fields of education.
21st International CDIO Conference Proceedings - Full Papers